Idiopathic non-cirrhotic intrahepatic portal hypertension in the West: a re-evaluation in 28 patients. Issue 2 (1st August 2002) - Hillaire, S; Bonte, E; Denninger, M-H; Casadevall, N; Cadranel, J-F; Lebrec, D; Valla, D; Degott, C
Abstract : Background: Non-cirrhotic portal hypertension of unknown cause is a poorly understood condition attributed to obstructive portal venopathy. Aim: To reassess the manifestations, course, and causes, with special attention to thrombosis. Methods: Analysis of a cohort of 28 patients. Results: Gastrointestinal bleeding occurred in 11 patients. Liver failure developed at the time of concurrent disease in eight patients, including all four patients who died. Portal vein thrombosis developed in 13 patients. A prothrombotic disorder was found in 12 of 23 fully investigated patients. Hepatoportal sclerosis was observed in 11 patients (with associated perisinusoidal fibrosis and/or nodular regenerative hyperplasia in six); periportal fibrosis, perisinusoidal fibrosis, nodular regenerative hyperplasia, or a combination thereof were observed in other patients. A morphometric evaluation showed an increased number of portal vessels in patients with hepatoportal sclerosis. There was no relation between pathological results and haemodynamic findings or prothrombotic disorders. Conclusions: Outcome was related to associated conditions. Overlap in pathological, haemodynamic, and causal features suggests a single entity, with prothrombotic disorders as major causal factors, and injury to sinusoids as well as to portal venules as the primary mechanism. Activated coagulation could mediate vascular injury in the absence of thrombosis. Anticoagulation should be considered.